GLOBALIZATION OF INFORMATION PROCESSES AS A DETERMINANT OF THE DEVELOPMENT OF THE INTERNATIONAL TOURISM MARKET - AVRIATA, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The globalization of information processes is one of the key determinants of modern economic development, and the tourism industry is no exception. Today, the international tourism market operates in the context of digital transformation, which is radically changing the mechanisms of its organization and management. The spread of the Internet, mobile applications, global booking systems, and online platforms has enabled the formation of a new model of interaction among travel companies, consumers, and state regulators. Information processes are a decisive factor in competitiveness in the international tourism market. The use of big data enables companies to create personalized offers, forecast demand, and enhance the quality of service. Online communication channels facilitate the integration of local tourism products into the global market, thereby reducing transaction costs. However, the globalization of information flows also presents several challenges: dependence on large international platforms, risks of cyber threats, manipulation of ratings and reviews, as well as digital inequality between countries and regions. Modern technologies are influencing the development of tourism products, enhancing their quality and accessibility. The introduction of new technologies not only enhances the level of service but also contributes to the sustainable development of tourism, making it more environmentally friendly, accessible, and comfortable for all categories of travelers. Tourism is not only a service industry but also an innovative approach to creating new needs and opportunities for people around the world. International institutions, particularly the World Tourism Organization (UNWTO), the European Union, and the Organization for Economic Cooperation and Development (OECD), play a crucial role in regulating information processes. Their activities are aimed at establishing transparency standards, protecting consumer rights, and introducing innovative technologies in the tourism sector. The globalization of information processes serves as a system-forming factor in the development of the international tourism market, creating new opportunities for business while simultaneously generating challenges that require comprehensive solutions at both national and international levels.